Home-based training program in patients with chronic heart failure and reduced ejection fraction: a randomized pilot study (Clinics, 2021)
OBJECTIVES: We aimed to compare the effects of home-and center-based exercise training programs on functional capacity, inspiratory muscle strength, daily physical activity level, and quality of life (QoL) in patients with chronic heart failure (CHF) over a 12-week period.METHODS: This study included 23 patients with CHF (left ventricular ejection fraction 31±6%) randomized to a home-based (n=11) or center-based (n=12) program. Patients underwent 12 weeks of aerobic training (60%-70% heart rate reserve): walking for the home-based and supervised cycling for the center-based group, both combined with resistance training (50% of 1 maximum repetition). At baseline and after 12 weeks of training, we assessed cardiopulmonary test variables, 6-min walk test distance (6 MWD), steps/day with accelerometry, and QoL (Minnesota Living with Heart Failure questionnaire). Maximal inspiratory pressure and handgrip strength were measured at baseline and after 4, 8, and 12 weeks of training. ClinicalTrials.gov: NCT03615157.RESULTS: There were no adverse events during training in either group. The home- and center-based training groups obtained similar improvements in peak oxygen uptake, maximal ventilation, and 6 MWD. However, there were significant between-group differences: center-based training was more effective in improving maximal inspiratory pressure (p=0.042), number of steps/day (p=0.001), and QoL (p=0.039).CONCLUSIONS: Home-based training is safe and can be an alternative to improve the exercise capacity of patients with stable CHF. However, center-based training was superior in improving inspiratory muscle strength, QoL, and daily physical activity.